The Role of Taman Pendidikan Al-Qur’an in Children’s Spiritual Development - Bambang Irawan; Alimni Alimni; Yesi Agustina; Andini Fadlillah; Sholilha Tussakdiah (JMiE (Journal of Management in Education), 2024)
This study examines the role of Taman Pendidikan Al-Qur’an (TPQ) in developing children’s spiritual values at Masjid Al Ikhlas, Jalan Semangka 3, Panorama Subdistrict, Singgaran Pati District, Bengkulu City. A qualitative descriptive approach was employed to explore spiritual development practices implemented through nonformal Islamic education. Data were collected through observations, interviews with teachers and administrators, and documentation of learning activities. The findings reveal that TPQ contributes significantly to children’s spiritual formation through Qur’anic learning, worship habituation, moral guidance, and exemplary behavior demonstrated by educators. Learning activities emphasize value internalization, religious discipline, and character development rather than cognitive mastery alone. Support from the mosque environment, parental involvement, and community participation strengthens the effectiveness of spiritual education. The study concludes that TPQ functions as an essential nonformal educational institution in fostering children’s spiritual awareness, moral conduct, and consistent religious practice.